The benefit of the Arabidopsis halleri ssp. gemmifera root exudate in cadmium extraction from the cadmium contaminated soil - Agni Lili Ariyanti; Mei-Fang Chien; Chihiro Inoue (Journal of Degraded and Mining Lands Management, 2023)
This study focuses on how to solve cadmium (Cd) contamination in soil because this contaminant decreases soil quality. Soil remediation using the hyperaccumulator plants is an optional process to solve soil contamination. Arabidopsis halleri ssp. gemmifera (hereinafter referred to as A. halleri), is one of the candidate plants expected to be used for phytoremediation of Cd contaminated soil. The A. halleri promote solubilization of Cd in the soil directly or indirectly using its secreted root exudate. However, the effect of the metabolites profile of this plant to Cd uptake from contaminated soil is still unclear. The purpose of this study is to examine the contribution of root exudates of A. halleri to extract Cd in the soil. Cd-contaminated soil used in this study was a farmland soil containing 5.8 mg kg-1 of Cd and 648 mg kg-1 of Zn taken from Tome City, Miyagi Prefecture, Japan. Soil leaching tests were conducted using the solution containing the root exudates from A. halleri plant. The accelerating effect of root exudates of A. halleri on solubilization of Cd is fundamental information to construct the benefit of phytoremediation.